Women Empowerment through Ecotourism Activities in Lower Kinabatangan Area of Sabah, East Malaysia (Journal of Governance and Development (JGD), 2017)
In Malaysia, women participation in ecotourism activities is a growing phenomenon, yet studies in this area are still in their infancy. Consequently, this paper seeks to identify women participation in ecotourism activities that empower them to be involved actively. Guided by Scheyvens’s Empowerment Framework (SEF), this study has identified several factors that contributed positively towards their participation in ecotourism activities as well as empower them at four levels such as psychological, social, political and economic. This study was carried out in Abai Village, Lower Kinabatangan, Sabah, from September to November 2014. Primary data were collected through face-to-face in-depth interviews with the women who were engaged in ecotourism activities in Abai Village. In addition, field observations and secondary resources were also utilised to strengthen the research findings. The findings revealed that, women in Abai Village are seriously and actively involved in ecotourism activities, and then this involvement has directly or indirectly empowered them aforementioned empowerment’s levels. This study has significant contributions to the tourism industry in Malaysia, where women participation in development projects such as ecotourism activities in rural areas of Malaysia enhances their lifestyle politically, economically, psychologically and socially.